An Analysis of Language Style Used in the Business and Investment Section of en.antaranews.com - Shelly Kustanti; Hiqma Nur Agustina (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2026)
This research aims to identify and analyze the language styles that are used in the online news as a mass media in the form of digital. As a human, language is one of the most important elements of their life. The language itself has the function of communicating with each other. The communication its purpose to share the information between one to other people. In order to share information on a large scale, there are mass media. There are several types of mass media that are commonly used by humans such as television, internet, magazine, newspaper, radio etc. In modern era, various aspects of life have transitioned into the digital era. Nowadays, many news agencies have formed online news platforms in order to replace the traditional form of printed news with a digital form. It also identifies the dominant language style that is being used in the news article, especially in the business and investment sections. The researcher uses qualitative approach. Its research uses document analysis as a technique for data collection. This research analyses the rhetorical style as the language style in the news article. The result of this research shows that there are 7 types of rhetorical styles that are used in the news article of Antara News, such as anastrophe, asyndeton, ellipsis, erotesis, euphemism, pleonasm, and tautology. Moreover, anastrophe is found to be the dominant type. This research can be used as a comparative analysis for future research in terms of language style, especially in mass media.